A metric profile of research highlighting teacher training in Science Education in Brazil - Razera, Julio César Castilho (2019)
This paper focuses on what current literature indicates about the need to learn about the teacher training research field in a wide-ranging and profound manner. Within this framework, the objective was to outline a metric profile of the research field of teacher training in Science Education in Brazil, based on articles from journals in this field. This project is part of extensive research on the subject, in which we make use of theoretical and methodological bases of descriptive statistics, bibliometrics and scientometrics. In this research, 406 articles on teacher training published in the following five Brazilian Science Education journals were analysed, from their first issue until the last issue of 2016: IENCI, Ciência & Educação, Ensaio, RBPEC and Alexandria. The set of indicators shows that the field merges own attributes (e.g. type of underlying literature; strong presence of female authors) with characteristics that are shared with other fields (e.g. distribution of productivity on a specific topic). The analyses performed suggest a profile of little theoretical production and low epistemic autonomy of the research field of teacher training in Science Education. There is clear import and use of theoretical and methodological references from other fields of research, particularly Education, Philosophy and Psychology.